Low voltage switched-capacitive-based reconfigurable charge pumps for energy harvesting systems: An overview - Ho, Tian Siang (IEEE-Inst Electrical Electronics Engineers Inc, 2022)
Conventional SC-based charge pump with fixed conversion ratio is predominantly adopted in energy harvesting (EH) systems, which becomes a bottleneck for attaining high power conversion efficiency (PCE) with wide dynamic range (WDR). This article reviews and explores the SC-based reconfigurable charge pump (RCP) as an alternative voltage-boosting element for the EH system. An overview of the RCP structure is established, followed by a comprehensive review of CP reconfigurable topologies along with state-of-art architecture. Design consideration of the RCP in terms of dynamic range, PCE, and VCE is provided to give a clear insight into the future development of RCP architecture for the EH system.